Sistem Informasi Geografis (SIG) Lokasi UMKM Berbasis Android Guna Meningkatkan Perekonomian UMKM - Ahmad Ismail; Nadila Nadila; M. Irwan Firdaus Irwan; Muh Syamsir; Muh Habibie Syahid B; Muh Faiq Qushasyi (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2021)
Public Geographic Information System (GIS) or Geographic Information System (GIS) is a computer-based information system that is used to process and store geographic-based data or information. This work program aims to design a geographic information system to determine micro, small and medium-sized businesses based on Android. Therefore, it can be accessed by the community to make it easier for people to know the location of micro, small and medium enterprises in Paccerakang Village, Makassar City, and can be accessed by people who need it. Information services globally. The data used in this work program is to collect data on SME actors in Biringkanaya District, Paccerakg Village using Google Maps, interviews with shop owners, data collection of coordinate points, and some other supporting data. The result of this work program is that a web-based SME store geographic information system has been built using Google Maps. Which makes it easy for web users to find out the position of the SME store, in which there is store information, store position, goods sold, and directions to the desired store.